Gait variability predicts cognitive impairment in older adults with subclinical cerebral small vessel disease - Mukli, Peter; Detwiler, Sam; Owens, Cameron D.; Csipo, Tamas; Lipecz, Agnes; Pinto, Camila Bonin; Tarantini, Stefano; Nyul-Toth, Adam; Balasubramanian, Priya; Hoffmeister, Jordan R.; Csiszar, Anna; Ungvari, Zoltan; et al. (Frontiers in Aging Neuroscience, 2022)
Introduction Advanced methods of gait research, including approaches to quantify variability, and orderliness/regularity/predictability, are increasingly used to identify patients at risk for the development of cognitive impairment. Cerebral small vessel disease (CSVD) is highly prevalent in older adults and is known to contribute to the development of vascular cognitive impairment and dementia (VCID). Studies in preclinical models demonstrate that subclinical alterations precede CSVD-related cognitive impairment in gait coordination. In humans, CSVD also associates with gait abnormalities. The present study was designed to test the hypothesis that increased gait variability and gait asymmetry predict a decline in cognitive performance in older adults with CSVD. Methods To test this hypothesis, we compared cognitive performance and gait function in patients with CSVD (age: 69.8 ± 5.3 years; n = 11) and age- and sex-matched control participants (age: 70.7 ± 5.8 years; n = 11). Based on imaging findings, patients with CSVD were identified [presence of white matter hyperintensities plus silent brain infarcts and/or microhemorrhages on magnetic resonance imaging (MRI) assessment]. Cognitive performance was assessed using the Cambridge Neuropsychological Test Automated Battery (CANTAB). Gait parameters were measured during the single and dual tasks, during which participants, in addition to the motor task, completed a series of mental arithmetic calculations. Spatial and temporal parameters of gait variability, symmetry, and permutation entropy were determined using a pressure-sensitive gait mat during single and dual cognitive task conditions. Results Patients with CSVD exhibited lower performance in a visual learning test (p = 0.030) and in a sustained attention test (p = 0.007). CSVD also affected step time variability (p = 0.009) and step length variability (p = 0.017). Step lengths of CSVD participants were more asymmetric (p = 0.043) than that of controls, while the two groups were statistically similar regarding step time symmetry and entropy of step time and length. Gait variability was inversely associated with sustained attention, especially among CSVD patients, and this relationship was significantly different between the two groups. The association of sustained attention with gait symmetry was also significantly different between the two groups. Discussion Our findings provide additional evidence in support of the concept that increased gait variability and asymmetry may predict cognitive impairment in older adults with CSVD.